HERMENEUTIKA SUFISTIK: TELAAH EPISTEMOLOGI TAKWIL IBN ‘ARABI - Haq, Sansan Ziaul (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Da'wah of IAIN Langsa, 2019)
The validity of Ibn ?Arabi?s ta?wil is much debated by experts, as is ishari interpretationin general. Some academics regard it as a deconstructive interpretation which subdues the Qur'anic text to mystical-gnostic teachings. But not a few argue that his mystical interpretation is in harmony with the principle of textuality. This article will discuss the epistemological construction of Ibn ?Arabi? ta?wil through an analysis of the hermeneutical assumptions he introduced. By using hermeneutic and sufistic psychology approaches, this qualitative research concludes that the ta?wil practiced by Ibn ?Arabi is a dialectical process between text and psychic-spiritual context, thus capturing various meanings in the Holy Text as a reflection of multi-dimensional reality. This kind of interpretation is literal because it imparts textual meaning, andat the same time spiritual because it also reaches inner unveiling.